PP2A and Its Inhibitors in Helper T-Cell Differentiation and Autoimmunity - Khan Mohd Moin; Kalim Ubaid Ullah; Khan Meraj H; Lahesmaa Riitta (FRONTIERS MEDIA SA, 2022)
Protein phosphatase 2A (PP2A) is a highly complex heterotrimeric Ser/Thr phosphatase that regulates many cellular processes. The role of PP2A as a tumor suppressor has been extensively studied and reviewed. However, emerging evidence suggests PP2A constrains inflammatory responses and is important in autoimmune and neuroinflammatory diseases. Here, we reviewed the existing literature on the role of PP2A in T-cell differentiation and autoimmunity. We have also discussed the modulation of PP2A activity by endogenous inhibitors and its small-molecule activators as potential therapeutic approaches against autoimmunity.